Updates on 2016 CNS tumor classification - Where do we stand? - Kolakshyapati, Manish; Shrestha, Tejashwi; Singh, Anish Man; Adhikari, Rupendra Bahadur; Shrestha, Prabin (Grande Medical Journal, 2019)
The updated 2016 World Health Organization (WHO) classification of central nervous system (CNS) tumors has incorporated the molecular markers together with histological parameters in defining and diagnosing various tumor entities. This has led to major changes and revision of the classification. A number of new entities are classified based on clinical, diagnostic, and prognostic relevance and those without such relevance have been removed. Major changes are incorporated in diffuse glioma, medulloblastoma, pediatric gliomas, and other embryonal tumors. These new requisites make molecular testing a basic requirement for CNS tumor diagnosis and treatment. New treatment protocols are designed and targeted based on the genetic alteration involved in the tumor entity. The update aims to achieve accurate diagnosis, determine precise prognosis and ensure better patient treatment all through facilitating better categorization of clinical and experimental trials. The multidisciplinary team of clinicians treating such tumor patients in a developing country like Nepal should try to adopt this updated version of the classification so as to improve and upgrade the neuro-oncological services to meet the international standards.